Farklı Sektördeki Ambalajların Tasarımındaki Renklerin Tüketici Tercihlerine Etkisinin İncelenmesi - ÖZDEMİR, LUTFİ; URAL, ELİF; ÖZOMAY, ZAFER; ÖZAKHUN, ŞÜKRÜ CEM (My University, 2016)
Basic functions of the packaging; transporting, protecting and introducing a product. Packaging is a very important fact in today’s increasingly competitive./increased competition. For the sale of packaged products. In addition to the structural features as well as visual attention needs to be supplemented with attractive and creative ideas. Product that ready for sale, should have convincing features to the consumer. Today, packages look like each other in terms of graphic design. These similarities, complicates the selection of product by consumer. The most important impact on the consumer of packaging design; the color of the packaging. Color represent; product’s brand value, identity and reflect the character of the determined image visually. Also; color is the most important tool to separate a product and packaging from each other. In this project; consumers purchasing reactions to packagings color ,tested according to these different industries; delicatessen, cleaning product, food, etc. In this project, for achieving general results ‘’descriptive scanning model’’is used. In the research; there are 40 woman and 30 men, totally 70 people. Researchers prepared a questionnaire that includes 47 question. In the analysis of data, percentages and frequency values are given for each item and cross tables were applied. The obtained data have been determinated according to the criteria representing the consumer profile. Obtained datas from test evaluated and shared.

Ambalajın temel fonksiyonları; bir ürünün taşınması, korunması ve tanıtılmasıdır. Ambalaj günümüzde artan rekabet içinde çok önemli bir olgudur. Ambalajlanmış ürünlerin satılması için; yapısal özelliklerinin yanı sıra görsel olarak ilgi çekici ve yaratıcı fikirlerle desteklenmesi gerekmektedir. Satışa hazır ürün müşteriyi ikna edici nitelikte olmalıdır. Günümüzde, ambalajlar tasarım noktasında birbirine benzemektedir. Bu benzerlik tüketicinin ürünü seçimini de zorlaştırmaktadır. Ambalaj tasarımının tüketici üzerindeki en önemli etkisi; ambalajın renk etkisidir. Renk ürünün marka değerini, kimliğini, karakterini yansıtmak için belirlenen imgeyi görsel olarak ifade eder. Ayrıca renk bir ürünü ve ambalajı diğerinden ayıran en önemli araçtır. Bu çalışmada; tüketicilerin ambalajın rengine olan satın alma tepkileri şarküteri, temizlik ürünü, gıda gibi farklı sektörlere göre test edilmiştir. Yapılan çalışmada, genelleştirilebilir sonuçlara ulaşılabilmesi amacıyla “betimsel tarama modeli” kullanılmıştır. Araştırmada 40 Kadın ve 30 erkek olmak üzere 70 kişiye ulaşılabilmiştir. Verilerin toplanmasında ilgili literatür ve araştırmalar ışığında araştırmacılar tarafından 47 soruluk bir anket hazırlanmıştır. Verilerin analizinde her bir maddeye ilişkin yüzde ve frekans değerleri verilmiştir ve çapraz tablolar uygulanmıştır. Elde edilen veriler, tüketici profilini temsil eden kriterlere göre test edilmiştir. Testler uygulanarak elde edilen veriler, değerlendirilerek sonuçlar paylaşılmıştır.
Investigation of the effect of color on consumers Preferences in packaging design at different sectors
Keywords: Color; Packaging; Design; Renk; Ambalaj; Tasarım